Influence of dough ingredients on 3-Mcpd formation in toast - C. M Breitling-Utzmann; H. Hrenn; N. U Haase; G. M Unbehend (Czech Journal of Food Sciences, 2004)
The influences of both traditional dough ingredients like fat and salt and a commercially used baking agent on the formation of 3-chloropropane-1,2-diol (3-MCPD) during toasting of bread were investigated. Whereas varying the fat or salt contents within technologically practicable limits showed negligible effects on 3-MCPD formation, the baking agent turned out to have a crucial impact on generating 3-MCPD in toasted bread slices. We found considerable evidence that the baking agent's main component saccharose was the major cause for its boosting the 3-MCPD formation. Emulsifiers like mono- and diacylglycerols or lecithin did not have any significant influence. 3-MCPD formation showed good correlation with the degree of browning of the bread slices; their 3-MCPD content increased exponentially towards dark brown coloured toasts. The relative proportions between 3-MCPD and 2-MCPD were an average of 3:1 in all samples. Dichloropropanols like e.g. 1,3-dichloropropan-2-ol could not be detected.